Visualizations during arithmetic tasks hamper performance and increase cognitive load in 9-year-olds: an fNIRS study - Skau, Simon; Karlsson, Jimmy; Åsberg Johnels, Jakob; Helenius, Ola (Frontiers in Psychology, 2026)
This study investigates whether visual aids increase or decrease cognitive load during arithmetic tasks in 9-year-old children, using behavioral measures and functional near-infrared spectroscopy (fNIRS). Previous research suggests mixed outcomes regarding whether visual aids increase or reduce cognitive load in educational tasks. In this experiment, children (N = 81) completed arithmetic tasks under varying conditions: text-based tasks, visual aid tasks, and irrelevant visual information tasks, all under low and high cognitive load and controlled for arithmetic content. Contrary to our preregistered hypothesis, tasks with visual aids resulted in more errors, longer time to answer, and increased functional activity in the prefrontal cortex (PFC) compared to only text-based tasks, suggesting that visual aids increased cognitive load. Scores on tasks with irrelevant visual information were equivalent to text-based tasks, but time to answer was slower. Implications for future research on cognitive load and theories about cognitive load are discussed, especially what to control for and the distinction between intrinsic and extraneous load.